Agile Project Management: Implementattion of Agile Working System in Bank Daya Usaha Sharia - Hanan Yulianto; Aries F Firman (Publikasi Indonesia, 2021)
Bank Daya Usaha Sharia as one of player in banking industry, experiencing with intense competition along with digitalization trend in banking industry so that competitor not only came from other bank but also come from internet and telecommunication industry. Bank Daya Usaha Sharia internally have treat which is slow to access or penetrate the market so that selected agile project management as working system because the methodology or approach already proven. Research questions related to condition Bank Daya Usaha Sharia are which working unit can implementation agile project management, what kind of agile methodology that is relevance and how agile project management can be implemented or what kind of factor influenced. Based on those questions, this research have objective to find out which working unit can implemented agile project management with relevance agile methodology and find out factors influenced that implementation. This research using qualitative research approach through interview, interview has conducted for eight (8) respondents, which is employee at Bank Daya Usaha Sharia at many level of position from department head, division head and director. With this interview, expected discover information about type project, project characteristic, project strategy and factors influenced in implementation agile project management. To determine type of project and project characteristic, use an approach Project Characteristic Quadrants by Goal and Solution Uncertainty, while to determine project strategy using approach Project Management Strategies Based on Complexity and Uncertainty. This research only conducted for four (4) working unit, among others Human Capital, Internal Audit, Business Risk & Development and Business Planning. Based on interview result and analysis, there are conclusions, such as working unit that possible implemented Agile Project Management are Human Capital, Business Risk & Development and Business Planning with Agile Methodology SCRUM, while Internal Audit more appropriate to implemented traditional project management. Thirteen (13) factors influenced in Agile Project Management implementation such as requirement, goals, solutions, team members, collaborative, directions, adapt to change, empowerment, agile mindset and organization drive. While reason why Bank Daya Usaha Sharia selected Agile Project Management as working system and implemented at current are competition, investment and best practice.